The freshwater snake eel genus Lamnostoma (Anguilliformes: Ophichthidae) in Taiwan, with description of a new species - Chiu, Yung-Chieh; Shao, Kwang-Tsao; Huang, Shih-Pin; Chen, Hong-Ming (Zootaxa, 2018)
A review of the freshwater ophichthid eel genus Lamnostoma from Taiwan is provided with three species recognized. Lamnostoma mindora has been recorded in previous literature and its presence is confirmed. Two specimens of Lamnostoma polyophthalmum represent the first record in Taiwan. A new species, Lamnostoma taiwanense sp. nov., is described on the basis of two specimens collected from northeastern Taiwan. It can be distinguished by having 3 preopercular pores, higher number of teeth on lower jaw, and a series of white spots with hill-shaped papillae along the head. A key to all known species of Lamnostoma is provided.